Instrumen Penilaian Hasil Pembelajaran Kognitif Pada Tes Objektif - Engel Novita Ramadani; Dina Fitria Handayani (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Assessment in education is very important to determine the achievement of educational goals, with continuous evaluation referring to comprehensive results. One of the assessment domains is the cognitive domain, which measures students' mastery of knowledge and critical thinking abilities, including problem solving. This research examines instruments for assessing cognitive learning outcomes in description and objective tests through literature study, using references from books, journals and related government regulatory documents. The research results show that the cognitive domain includes mental activities that focus on the ability to connect and combine various ideas or methods to solve problems. Written objective tests, which consist of true-false, multiple choice, matching, and complete/short answer, are important for accurately measuring cognitive aspects in the learning process.